2006
DOI: 10.1007/s00122-006-0330-2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic mapping reveals a single major QTL for bacterial wilt resistance in Italian ryegrass (Lolium multiflorum Lam.)

Abstract: Bacterial wilt caused by Xanthomonas translucens pv. graminis (Xtg) is a major disease of economically important forage crops such as ryegrasses and fescues. Targeted breeding based on seedling inoculation has resulted in cultivars with considerable levels of resistance. However, the mechanisms of inheritance of resistance are poorly understood and further breeding progress is difficult to obtain. This study aimed to assess the relevance of the seedling screening in the glasshouse for adult plant resistance in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
63
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 57 publications
0
63
2
Order By: Relevance
“…Out of 2,761 probes, which scored positively in L. multiflorum, 529 DArT markers were placed on its genetic map ). This significantly enriched original genetic map generated with a total 352 other markers (Studer et al 2006). In L. perenne, 297 DArT markers were genetically mapped with a total map length of 966 cM (Tomaszewski et al 2011).…”
Section: Genetic and Physical Mappingmentioning
confidence: 97%
“…Out of 2,761 probes, which scored positively in L. multiflorum, 529 DArT markers were placed on its genetic map ). This significantly enriched original genetic map generated with a total 352 other markers (Studer et al 2006). In L. perenne, 297 DArT markers were genetically mapped with a total map length of 966 cM (Tomaszewski et al 2011).…”
Section: Genetic and Physical Mappingmentioning
confidence: 97%
“…QTL analyses in a mapping population of L. multiflorum have demonstrated that bacterial wilt resistance is controlled by one major QTL on linkage group (LG) 4 explaining between 43 and 84 % of the total phenotypic variance for resistance (Studer et al 2006). Phenotypic traits that result in the identification of one single QTL explaining such a high percentage of the total observed phenotypic variance have often been shown to be controlled by one or only a few major R-genes (Mutlu et al 2006).…”
Section: Genetic Control Of Bacterial Wilt Resistance In L Multiflorummentioning
confidence: 99%
“…Molecular genetic tools for discovering and targeting genes and alleles in germplasm collections and/or breeding lines have the potential to enhance the efficiency of breeding programs through marker assisted selection (MAS). Although a number of quantitative trait loci (QTL) associated with resistance to diseases such as crown rust and bacterial wilt have been identified in L. perenne and L. multiflorum (Dracatos et al 2010;Studer et al 2006), so far no example of successful MAS has been reported for these species. This may arise from the narrow genetic base of mapping families when compared to the range of variation available in the breeding germplasm or the often unknown genetic composition of pathogen populations (Dracatos et al 2006;Kölliker et al 2006).…”
Section: Introductionmentioning
confidence: 98%
“…In Italian ryegrass, genetic markers linked with resistance to crown rust, ryegrass blast, and bacterial wilt (Xanthomonas translucens pv. graminis) have been developed by using molecular genetic maps based on several types of markers (Fujimori et al 2004, Miura et al 2005, Studer et al 2006. However, most of these markers are not directly associated with genes that control agronomically important traits, because most of the marker loci were obtained from bands that were randomly amplified from non-functional sequences of genomic DNA.…”
Section: Introductionmentioning
confidence: 99%